Perspectives on tax reform in Brazil - Marc Morgan (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
There is no question that the salience of tax reform in Brazil is high. It has become common to point out the country's low quality of public services and high level of taxes, at least from the view of the country's 'middle class' and poorer income groups. In this context it would be desirable to introduce new ways of thinking about matters related to government policy generally, and tax policy more specifically. By understanding the function and potential of taxes, as well as their links to inequality and economic development, the seed can be planted for deep change. Once we conceptualise the potential of certain policies, momentum can be garnered to fully realise them if they are desirable to a majority of the population. [...]
Keywords: 330; Perspectives; reform; Brazil